Geospatial information technology for sustainable forest development in Malaysia / Kamaruzaman Jusoff - Jusoff, Kamaruzaman (2002)
Growing Malaysian population density lead to scarcity of forest land and widespread changes in forestry land use leading to widespread environmental problems. To solve these problems and to make sure that future generations can enjoy the benefits of the Malaysia's forest resources, better and more careful sustainable development of our forest resources is needed. In the establishment of sustainable development of this forest resources, planners, managers, policy makers and researchers alike need to understand the complexity of factors involved. They must collect and interpret the required data and work together with professionals from other disciplinary fields. Geospatial information technology and especially remote sensing, plays an important role in these tasks. The objective of this paper is therefore to illustrate the usefulness of remote sensing technology in providing a synoptic view and spatial geo-information for sustainable forest development in Malaysia. Specific attention is given to some selected successful case studies involving mapping deforestation in permanent forest reserves (PFR's), forest type and forest land use classifications, forest inventory, forest recreation planning, water turbidity in dams, forest road and timber harvesting. Modem remote sensing (RS) techniques including airborne hyperspectral sensing were digitally analysed and integrated with geographic information system (GIS) and global positioning system (GPS) to collect, quantify and map in a statistically acceptable and sound way, geo-referenced information to support sustainable forest development. The paper also presented a spectrum of recent developments in spatial data capture and analysis techniques in the RS of forest condition. Results indicated that optical data sets such as LANDSAT TM and SPOT imagery provide macro level forest information such as forest fire planning and inventory, airborne radar AlRSAR-TOPSAR data provides the opportunity to penetrate the forest canopy and assess attributes to forest type land cover mapping, high-resolution imagery such of IKONOS-I data provides mapping of precise wetland forest, hyperspectral scanners can map individual forest trees/species and change detection which provides efficient, statistically based means of quantifying trends in forest condition. Some interesting and innovative developments in RS such as those presented in this paper show considerable promise in this area.